Cardiac adaptation to hypertension in adult female Dahl salt‐sensitive rats is dependent on ovarian function, but loss of ovarian function does not predict early maladaptation. Issue 3 (8th February 2018) - Ludvigsen, Stian; Mancusi, Costantino; Kildal, Simon; de Simone, Giovanni; Gerdts, Eva; Ytrehus, Kirsti
Abstract: Aim of study was to examine experimentally the adult female hypertensive heart in order to determine the role of ovary function in the response of the heart to salt‐dependent hypertension. Dahl salt‐sensitive rats, age 12 weeks, with/without ovariectomy were fed a standard (0.3% NaCl) or high‐salt diet (8%) for 16 weeks. Mean arterial blood pressure monitored noninvasively in conscious state increased significantly by high salt. Echocardiography was performed at baseline and endpoint. Heart function and molecular changes were evaluated at endpoint by left ventricle catheterization, by sirius red staining for collagen and by gene expression using quantitative RT‐PCR for selected genes. At endpoint, significant concentric hypertrophy was present with high salt. Increase in relative wall thickening with high salt compared to normal diet was more pronounced with intact ovaries (0.33 ± 0.02 and 0.57 ± 0.04 vs. 0.29 ± 0.00 and 0.46 ± 0.03) as was the reduction in midwall fractional shortening (20 ± 0.6 and 14 ± 2 vs. 19 ± 0.9 and 18 ± 1). Ovariectomy increased stroke volume and decreased the ratio of mitral peak velocity of early filling ( E ) to early diastolic mitral annular velocity ( E ′) ( E / E ' ratio) when compared to hearts from intact rats. High salt increased expression of collagen I and III genes and perivascular collagen in the heart slightly, but % interstitial collagen by sirius red staining remained unchanged in intact rats and decreased significantly by ovariectomy. Added volume load but not deterioration of function or structure characterized the nonfailing hypertensive heart of salt‐sensitive females ovariectomized at mature age when compared to corresponding intact females. Abstract : Hearts of female Dahl salt‐sensitive hypertensive rats were studied using echocardiography, left ventricular pressure volume loops, gene expression, and collagen expression. Hypertensive ovariectomized Dahl salt‐sensitive females showed a circulatory response with increase in heart work combined with tendency to better‐maintained midwall fractional shortening in spite similar degree of compensatory LV hypertrophy and perivascular fibrosis when compared with intact hypertensive females. This is might be an energy demanding situation and strengthens the need for better understanding of ovarian function in cardiac adaption to salt‐dependent hypertension in the female.